Matharpacady-29.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Every year new installations are made by the residents of Matharpacady during Christmas, entirely handmade by them. The sleigh is pulled by the reindeer Rudolf and Dasher, and driven by Santa Claus across the night sky. The sleigh was very popular with the neighbourhood children who were thrilled to take a ride on it and get their pictures clicked.